Home Based Trip Generation Model S Analysis in Medan, Binjai, Deli Serdang and Karo (Mebidangro) Urban Area, Indonesia - Agustinus Panjaitan; Abdul Rahim Matondang; Marlon Sihombing; Agus Purwoko (Journal of World Conference (JWC), 2020)
The purpose of this research is to develop a home-based trip generation model and analyze the variables that influence the trip generation model of people. This study focuses on the trip generation of home-based people in the Medan-Binjai-Deli Serdang (Mebidang) area so that the sample to be used in households that make home-based trips in the region. The mathematical model that generated regression with the dependent variable the number of home-based trips affected by several independent variables that influence it. The resulting model was then validated by the VIF and Anova tests and the Heteroscedasticity test. From the results of this study, it is expected that a trip generation model of home-based trip generation in the Mebidang urban area will be generated so that it can be known what factors influence the trip generation of the area.